Cefepime/Sulbactam — A New Innovative Antibiotic for In-Hospital Treatment of Severe Infections and the Implementation of Carbapenem-Replacement Strategy to Contain Antibiotic Resistance - S. V. Yakovlev; M. P. Suvorova; A. O. Bykov (Антибиотики и Химиотерапия)
Cefepime/sulbactam is a combined antibiotic consisting of the 4 th generation cephalosporin cefepime and the beta-lactamase inhibitor sulbactam in 1:1 ratio. Cefepime/sulbactam antibiotic was developed in Russia in 2006, it had passed preclinical and clinical studies, was approved for medical use, and has been produced in Russia since 2019. Cefepime has a wide spectrum of antimicrobial activity against gram-positive and gram-negative microorganisms, sulbactam adds two clinically important pathogens to the antimicrobial spectrum of cefepime — Acinetobacter baumannii and Bacteroides fragilis. In addition, sulbactam protects cefepime from hydrolysis by class A broad- and extended-spectrum beta-lactamases, and cefepime itself is stable against class C chromosomal beta-lactamases and partially stable to OXA-type class D carbapenemases. In vitro studies have shown that most clinical strains of ESBL-producing Klebsiella pneumoniae, Escherichia coli, Proteus spp. are sensitive to cefepime/sulbactam, as well as some strains of K.pneumoniae and A.baumannii that are resistant to carbapenems as a result of the production of class D carbapenemases. The efficacy and safety of cefepime/sulbactam have been determined in three clinical studies. Clinical and bacteriological efficacy of the drug was 97.9% and 97.6% in patients with acute community-acquired pyelonephritis. In the MAXI-19 multicenter study, the clinical efficacy of cefepime/sulbactam in patients with intra-abdominal infections, nosocomial pneumonia, and ventilator-associated pneumonia was 78.4, 90.3, and 80.7%, respectively. A comparative study examined the efficacy of cefepime/sulbactam and carbapenems in severe nosocomial infections (84% of patients had sepsis or septic shock). Clinical efficacy of cefepime/sulbactam and carbapenems was high and did not significantly differ (71% vs. 62%), as well as the bacteriological efficacy — 87% vs. 73%, while typical hospital pathogens characterized by MDR or XDR were identified in the majority of patients (most often — K.pneumoniae, A.baumannii, E.coli). During treatment with carbapenems, carbapenem-resistant bacteria were detected significantly more often (74.5%, most often A.baumannii — 44.7%, K.pneumoniae — 38.3%), compared to cefepime/sulbactam (20.0%, P.aeruginosa and K.pneumoniae, both at 15.5%), P=0.0001. The risk of superinfection was also significantly higher with carbapenems than with cefepime/sulbactam (53.3% vs. 22.2%, P=0.001). For severe infections, cefepime/sulbactam was administered at a dose of 4 g (2 g + 2 g) every 12 hours or 2 g (1 g + 1 g) every 8 hours. Currently, cefepime/sulbactam should be considered as a reliable option for the treatment of severe infections in the hospital as a carbapenem-replacement strategy to reduce the risks of selection of carbapenem-resistant gram-negative bacteria.